Використання комп’ютерних технологій у фінансовому плануванні - Бровко, Лариса Іванівна; Brovko, Larysa (Дніпровський державний аграрно-економічний університет, 2015)
Розглянуто особливості застосування сучасних комп’ютерних технологій, що сприяли б підвищенню ефективності та результативності процесу фінансового планування на підприємствах; надається визначення основних понять. Наведено порівняльну характеристику програмних продуктів, переваги та недоліки, а також описано фактори, що вказують на необхідність застосування автоматизованих систем планування в сільськогосподарських підприємствах. The article discusses the features of the application of modern computer technology that would contribute to the effectiveness and efficiency of the financial planning for businesses. There is also given the definition of basic concepts. There are comparative characteristics of software products, advantages and disadvantages, and describes the factors that point to the need of using the automated systems of planning for agricultural enterprises.Financial planning is one of the main forms of general planning, which includes the development and study of targets that characterize the development of economy in the coming period; economic standards, which can be expected in the planned period.The development of financial plan is a troublesome process and connected with many calculations. Even if the company produces a small product range, the financial planning process is time consuming, not to mention the usage of complex mathematical models and formulas.InUkrainethere are a number of software packages that are able to make easier the process of financial planning. A good program makes life easier saves valuable time and allows you to focus on planning and analysis.Each software package has its own strengths and weaknesses, and the final decision to buy it will largely base on user’s preferences and the needs and available financial resources in the enterprise. A program represented on the market varies on the price and its features, but obey the simple rule: you get what pay for.
Using computer technology in the financial planning
Keywords: фінансове планування; financial planning; розробка фінансового плану; developing of financial plan; автоматизація; automation; програмні продукти; software products; управлінське рішення; management decision